Influence of Alkaline Treatment with Ammonia Water on the Properties of PEDOT: PSS Films - Jiao Li; Hua Zhang; Juncheng Liu; Hui Qi (International Journal of Photoenergy)
A study on the influence of alkaline treatment on the properties of poly(3,4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT: PSS) film is presented in this paper. The treatment is carried out using ammonia water (AW) solutions with various volumes. We have also examined the performance of organic solar cells (OSCs) with the undoped and AW-doped PEDOT:PSS layers. Results show that the acidity of PEDOT:PSS solution can be significantly reduced by adding the AW solution with the optimized volume ratio ≤9%, v/v, while the AW-doped PEDOT:PSS film shows an improved optical transmission and stabilized conductivity. However, compared to the pristine OSC without adding AW to the whole-extraction layer, the AW-doped OSC shows a slight degradation in the power conversion efficiency (from 2.12% to 2.02%), which has been attributed to the decreased Vo